Use of effective training and quality assurance strategies is associated with high-fidelity EBI implementation in practice settings: a case analysis. Issue 1 (26th November 2019) - Dolcini, M Margaret; Davey-Rothwell, Melissa A; Singh, Ryan R; Catania, Joseph A; Gandelman, Alice A; Narayanan, Vasudha; Harris, Justin; McKay, Virginia R
Abstract : This paper presents methods for identifying what makes programs work (i.e., core functions and forms of programs) so that people implementing programs don't change what makes programs work as they are adapting programs to their organization/setting. Abstract: High-quality implementation of evidence-based interventions is important for program effectiveness and is influenced by training and quality assurance (QA). However, gaps in the literature contribute to a lack of guidance on training and supervision in practice settings, particularly when significant adaptations in programs occur. We examine training and QA in relationship to program fidelity among organizations delivering a widely disseminated HIV counseling and testing EBI in which significant adaptations occurred due to new testing technology. Using a maximum variation case study approach, we examined training and QA in organizations delivering the program with high- and low-fidelity (agencies: 3 = high; 3 = low). We identified themes that distinguished high- and low-fidelity agencies. For example, high-fidelity agencies more often employed a team approach to training; demonstrated use of effective QA strategies; leveraged training and QA to identify and adjust for fit problems, including challenges related to adaptations; and understood the distinctions between RESPECT and other testing programs. The associations between QA and fidelity were strong and straightforward, whereas the relationship between training and fidelity was more complex. Public health needs high-quality training and QA approaches that can address program fit and program adaptations. The study findings reinforced the value of using effective QA strategies. Future work should address methods of increasing program fit through training and QA, identify a set of QA strategies that maximize program fidelity and is feasible to implement, and identify low-cost supplemental training options.